Identification of a TMEM127 variant in a patient with paraganglioma and acromegaly. (23rd September 2020) - Stütz, Beryl; Korbonits, Marta; Kothbauer, Karl; Müller, Werner; Fischli, Stefan
Abstract : Summary: The coincidence of a pheochromocytoma or paraganglioma and a pituitary adenoma in the same patient is a rare condition. In the last few years SDH x and MAX mutations have been identified and discussed as a potential causal connection in cases of coincidence. We describe a case of a middle-aged female patient which presented with acromegaly, a growth hormone-secreting pituitary adenoma and a symptomatic neck paraganglioma. The patient was cured by surgery from both the pituitary tumour and the paraganglioma and is well after ten years follow-up. Due to the unusual coexistence of two neuroendocrine tumours, further molecular genetic testing was performed which revealed a variant in the TMEM127 gene (c245-10C>G). Learning points: Pheochromocytoma/paraganglioma and coexisting functioning pituitary adenoma are a very rare condition. An appropriate treatment of each tumour entity with a multi-disciplinary approach and regular follow-up is needed. The possibility of a hereditary disease should be considered and genetic workup is recommended. Genetic testing should focus primarily on the genes with mutations related to pheochromocytomas and paragangliomas. Next-generation sequencing with multi-gene panel testing is the currently suggested strategy. Genes associated with paragangliomas and pituitary adenomas are SDHA, SDHB, SDHC, SDHD, SDHAF2, MAX and MEN1, while case reports with VHL, RET and NF1 may represent coincidences. Variants of uncertain significance may need ongoing vigilance, in case novel data become available of these variants.